(untitled) (Journal of Face Aesthetics, 2020)
Introduction. The severity of facial wrinkles is related to many factors, such as: endogenic skin aging (innate mechanisms), the influence of external factors (photoaging) and lifestyle factors such as smoking or body weight. Aim. The aim of the study is to determine the relationship between BMI and the occurrence of various types of facial wrinkles. Material and Methods. 50 people participated in the study, including 9 men and 41 women. The criteria for participation in the study were: age over 18, no visible facial hair, no makeup. Each volunteer had their weight and height examined — BMI was determined and 6 extraoral photographs were taken. The severity of wrinkles in 9 facial areas was analyzed, and their severity was assessed on the basis of a photographic scale by three independent researchers. The obtained data were analyzed statistically. The adopted limit of statistical significance was p <0.05. Results. There was a statistically significant correlation between BMI and the severity of mouth angle wrinkles. Conclusions. The relationship between BMI and the severity of the wrinkles of the mouth angle may be determined by the weight of the subcutaneous tissue around the mouth angle, however, it requires more detailed research.